1999
DOI: 10.1364/ol.24.000466
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of optical synchronization of chaotic external-cavity laser diodes

Abstract: An experimental demonstration of optical synchronization of chaotic external-cavity semiconductor laser diodes is reported for what is believed to be the first time. It is shown that at an optimum coupling strength between the master and the slave lasers high-quality synchronization can be obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
46
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 160 publications
(46 citation statements)
references
References 10 publications
0
46
0
Order By: Relevance
“…Two coupled semiconductor lasers exhibit chaos synchronization. Different coupling setups such as unidirectional or mutual coupling and variations of the strength of the self and coupling feedback result in different synchronization states: the two lasers can synchronize in a leaderlaggard or anticipated mode [3,4], as well as in two different synchronization states; achronal synchronization in which the lasers assume a fluctuating leading role, or isochronal synchronization where there is no time delay between the two lasers' chaotic signals [2,5,6,7,8].In this Letter we focus on a symmetric setup, the time delay between the lasers is denoted by τ c and the time delay of the self-feedback is denoted by τ d . In the event of τ c = τ d = τ and for a wide range of the mutual coupling strength, σ, and the strength of the self-feedback, κ, the stationary solution is isochronal synchronization [2,5,9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two coupled semiconductor lasers exhibit chaos synchronization. Different coupling setups such as unidirectional or mutual coupling and variations of the strength of the self and coupling feedback result in different synchronization states: the two lasers can synchronize in a leaderlaggard or anticipated mode [3,4], as well as in two different synchronization states; achronal synchronization in which the lasers assume a fluctuating leading role, or isochronal synchronization where there is no time delay between the two lasers' chaotic signals [2,5,6,7,8].In this Letter we focus on a symmetric setup, the time delay between the lasers is denoted by τ c and the time delay of the self-feedback is denoted by τ d . In the event of τ c = τ d = τ and for a wide range of the mutual coupling strength, σ, and the strength of the self-feedback, κ, the stationary solution is isochronal synchronization [2,5,9].…”
mentioning
confidence: 99%
“…Two coupled semiconductor lasers exhibit chaos synchronization. Different coupling setups such as unidirectional or mutual coupling and variations of the strength of the self and coupling feedback result in different synchronization states: the two lasers can synchronize in a leaderlaggard or anticipated mode [3,4], as well as in two different synchronization states; achronal synchronization in which the lasers assume a fluctuating leading role, or isochronal synchronization where there is no time delay between the two lasers' chaotic signals [2,5,6,7,8].…”
mentioning
confidence: 99%
“…Most experimental investigations of chaos synchronization in unidirectionally coupled external cavity semiconductor lasers [4] have found that the lag time between the master and slave lasers' intensities is equal to the coupling delay, whereas numerical results [5] show that the lag time should be equal to the difference between the delay time in the coupling and round-trip time of the light in the transmitter's external cavity. Knowledge of the exact lag time is of considerable practical importance, as experiments on message transmission using fibre lasers and diode lasers have shown that the recovery of message at the receiver critically depends on the correction made for the lag time [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of the exact lag time is of considerable practical importance, as experiments on message transmission using fibre lasers and diode lasers have shown that the recovery of message at the receiver critically depends on the correction made for the lag time [4,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation